Two new species of Elaphoidella (Copepoda, Harpacticoida) from caves in southern Thailand and a key to the species of Southeast Asia - Watiroyram, Santi; Sanoamuang, La-Orsri; Brancelj, Anton (Zootaxa, 2017)
Elaphoidella paraaffinis sp. nov. and E. ligorae sp. nov. are described from Phra Kayang and Khao Plu caves respectively in southern Thailand. They both belong to Group I sensu Lang (1948). Elaphoidella paraaffinis and E. ligorae are similar to E. affinis Chappuis, 1933 and E. cabezasi Petkovski, 1982 respectively. Elaphoidella paraaffinis differs from E. affinis by (1) its larger sized setae on Exp P5, (2) the absence of an inner seta on Endp P1–P4, (3) fewer setae on P3 Endp-2, and (4) a larger number of ventral spinules on its anal segment. Elaphoidella ligorae differs from E. cabezasi by (1) its serrated posterior margins of urosomites, (2) the presence of strong inner spinules on its caudal ramus, (3) larger sized and a lower number of ventral spinules on its anal segment in male and female respectively, (4) larger sized setae on P5 in female, (5) the presence of an inner seta on Endp-1 P2, and (6) a larger number of setae on Endp-2 P2 in male. An identification key to the Southeast Asian species of the genus Elaphoidella Chappuis, 1929 is provided.